1997
DOI: 10.1046/j.1365-2796.1997.89104000.x
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐abdominal pressure, sagittal abdominal diameter and obesity comorbidity

Abstract: Objectives. To determine relationship of intraabdominal pressure to central obesity and the comorbidity of obesity. Design. Non‐randomized, prospective. Setting. University hospital, operating room. Subjects. Eighty‐four anaesthetized consecutive patients prior to gastric bypass for morbid obesity and five non‐obese patients before colectomy for ulcerative colitis. Main outcome measures. Weight, body mass index (BMI), co‐morbid history, sagittal abdominal diameter, waist:hip (W∶H) ratio and urinary bladder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
251
2
22

Year Published

2000
2000
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 440 publications
(288 citation statements)
references
References 28 publications
11
251
2
22
Order By: Relevance
“…Increased intra-abdominal pressure could be part of the explanation for the correlation of BMI and increasing severity of primary venous disease, such as first mentioned by Danielsson et al 1 That obese patients have an increase in intra-abdominal pressure was also shown by Sugerman et al, 16 who investigated urinary bladder pressure in morbidly obese patients under general anesthesia who were undergoing bypass surgery. They found that there was an increase in sagittal abdominal diameter that was associated with an increase in intra-abdominal pressure more so than the waist/hip ratio.…”
Section: Discussionmentioning
confidence: 85%
“…Increased intra-abdominal pressure could be part of the explanation for the correlation of BMI and increasing severity of primary venous disease, such as first mentioned by Danielsson et al 1 That obese patients have an increase in intra-abdominal pressure was also shown by Sugerman et al, 16 who investigated urinary bladder pressure in morbidly obese patients under general anesthesia who were undergoing bypass surgery. They found that there was an increase in sagittal abdominal diameter that was associated with an increase in intra-abdominal pressure more so than the waist/hip ratio.…”
Section: Discussionmentioning
confidence: 85%
“…We neither performed echocardiography to exclude heart diseases nor monitor the intra-abdominal pressure during the Doppler examination. The role of the intra-abdominal pressure in the magnitude of venous modulation is evidenced by a decrease in venous pulsatility when the patient is sitting and during deep inspiration, maneuvers known to increase intra-abdominal pressure (Sugerman et al 1997). …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, intra-abdominal pressure, which is directly related to the degree of abdominal adiposity, 66 may amplify the compression due to renal sinus lipomatosis. In lean rabbits, the kidneys lay partially submersed in the ventral surface of the retroperitoneal fat.…”
Section: Ectopic Fat Storage In the Kidneymentioning
confidence: 99%